2016
DOI: 10.1016/j.neuropharm.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Agonist and antagonist bind differently to 5-HT1A receptors during Alzheimer’s disease: A post-mortem study with PET radiopharmaceuticals

Abstract: PET imaging studies using 5-HT 1A receptor radiotracers show a decreased density of this receptor in hippocampi of patients with Alzheimer's disease (AD) at advanced stages. However, current 5-HT 1A receptor radiopharmaceuticals used in neuroimaging are antagonists, thought to bind to 5-HT 1A receptors in different functional states (i.e., both the one which displays high affinity for agonists and is thought to mediate receptor activation, as well as the state which has low affinity for agonists).Comparing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 57 publications
0
26
0
1
Order By: Relevance
“…[43] Based on the present data, it may be anticipated that NLX-112 preferentially activates 5-HT 1A receptors in those brain regions where they are coupled to Gao, including hippocampus. An autoradiographic study on post-mortem human brain sections showed that NLX-112 has clear agonist-like properties in this brain region [44] and other studies have shown that [ 18 F]NLX-112 has a distinctive pattern of in vivo micro-PET rat brain binding, with pronounced labelling of subcortical structures. [45] Such observations suggest that NLX-112 possesses G-protein activation and signal transduction properties that differentiate it from other 5-HT 1A agonists such as (AE)8-OH-DPAT, (+)8-OH-DPAT F15599 or F13714.…”
Section: Activation Of G-proteins In Hippocampal Membranesmentioning
confidence: 98%
“…[43] Based on the present data, it may be anticipated that NLX-112 preferentially activates 5-HT 1A receptors in those brain regions where they are coupled to Gao, including hippocampus. An autoradiographic study on post-mortem human brain sections showed that NLX-112 has clear agonist-like properties in this brain region [44] and other studies have shown that [ 18 F]NLX-112 has a distinctive pattern of in vivo micro-PET rat brain binding, with pronounced labelling of subcortical structures. [45] Such observations suggest that NLX-112 possesses G-protein activation and signal transduction properties that differentiate it from other 5-HT 1A agonists such as (AE)8-OH-DPAT, (+)8-OH-DPAT F15599 or F13714.…”
Section: Activation Of G-proteins In Hippocampal Membranesmentioning
confidence: 98%
“…Le développement récent de radiotraceurs 5-HT 1A agonistes a permis d'apporter les premiers éléments favorables à cette hypothèse. Ainsi, la comparaison de la fixation in vitro d'un agoniste 5-HT 1A , le [ 18 F]F13640, et de l'antagoniste correspondant, le [ 18 F] MPPF, a montré des différences de fixation sur des tissus cérébraux de sujets Alzheimer, indiquant un découplage des récepteurs à des stades précoces de la pathologie, avant que l'antagoniste ne révèle une diminution de la densité totale des récepteurs, à un stade de Braak plus avancé (Vidal et al, 2016). Après validation in vivo de ce radiotraceur agoniste dans différentes espèces animales (Vidal et al, 2018), une première étude chez l'Homme a été menée afin d'établir la preuve de concept de cette imagerie spécifique des récepteurs fonctionnels, c'est-àdire couplés à leurs protéines de transduction (Colom et al, 2019).…”
Section: Vers Une Imagerie Des Récepteurs Fonctionnels ?unclassified
“…One of these, F13640, was radiolabeled by replacing a non-radioactive fluorine-19 by a radioactive fluorine-18, [ 18 F]-F13640, with exactly the same chemical structure. Importantly, in-vitro autoradiographic studies showed that [ 18 F]-F13640 binding was drastically reduced by pharmacologic uncoupling of the receptor from its G-protein, indicating the agonist behavior of this molecule [6]. Under the same experimental conditions, [ 18 F]-MPPF, an antagonist of the same receptor, showed unchanged or slightly increased binding [6].…”
mentioning
confidence: 99%
“…Importantly, in-vitro autoradiographic studies showed that [ 18 F]-F13640 binding was drastically reduced by pharmacologic uncoupling of the receptor from its G-protein, indicating the agonist behavior of this molecule [6]. Under the same experimental conditions, [ 18 F]-MPPF, an antagonist of the same receptor, showed unchanged or slightly increased binding [6]. These autoradiographic experiments on human brain tissue provided encouraging results for this novel radiopharmacologic concept of targeting functional receptors by a radiolabeled agonist.…”
mentioning
confidence: 99%
See 1 more Smart Citation